Minor Visual Phenomena in Lewy Body Disease: A Systematic Review - Elettra Capogna; Virginia Pollarini; Alessia Quinzi; Lucia Guidi; Luisa Sambati; Maria Sasca Criante; Elena Mengoli; Annalena Venneri; Raffaele Lodi; Caterina Tonon; Micaela Mitolo (Biomedicines)
Minor visual phenomena (MVP), such as visual illusions, pareidolias, feeling of presence, and passage hallucinations, are often experienced by patients with Lewy Body Disease (LBD), in addition to complex visual hallucinations (VH), even in the early stages of the disease. This systematic review aimed to provide an up-to-date literature review of the occurrence and prevalence of MVP in LBD and to assess their potential associations both with VH and visuoperceptual and visuospatial deficits. A systematic literature search was carried out in PubMed, Web of Science, APA PsycInfo, Scopus, and Cochrane Library, and a total of 44 articles were included. The included studies showed significant variability in the occurrence of MVP in the LBD population and in the assessment methods used, such as standardized scales (e.g., the noise pareidolia test), semi-structured interviews (e.g., the North-East Visual Hallucinations Interview), and clinical descriptions. Similarly to VH, MVP appears to be highly specific to LBD, helping in differential diagnosis from Alzheimer’s Disease. The overall relationship between MVP, VH, and visuoperceptual/visuospatial deficits remains unclear. Some studies found that MVP (especially pareidolic responses and presence of hallucinations) was positively correlated with VH, yet it is challenging to determine whether MVP can be considered a precursor of future VH development. Negative associations were reported between MVP (especially pareidolias) and visuoperceptual/visuospatial abilities. However, it is not clear whether these deficits serve as independent, exclusive factors in MVP occurrence or if they interact with VH as a contributing component. Gaining insight into the occurrence of these phenomena could prove beneficial for differential diagnosis, prognosis, and prediction of treatment outcomes in patients with LBD.